Treatment of Gastric Epithelial Tumours by Endoscopic Submucosal Dissection Using an Insulated-Tip Diathermic Knife - Xu Li Hua; Qian Jun Bo; Gu Liu Gen; Lu Fei; Wang Ya Min; Li Yu Ming; Lu Hua Sheng (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic submucosal dissection (ESD) is a promising technique for the treatment of large, pre- and early malignant gastrointestinal lesions.